The Development of Teaching Materials for the Principles of Nonformal Education Based on Higher Order Thinking Skills on The Subject of Tasks and Population Goals of Non Formal Education - Yusnadi Yusnadi; Rosdiana Rosdiana; Anifah Anifah (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This research aims at generating: (1) the procedure of teaching material development (handbook) for the principles of nonformal education based on higher order thinking skills on the subject of population and education goals non formal education, and (2) the teaching materials for the principle of nonformal education based on higher order thinking skills on the Subject of Population and education goals that was valid to be used in learning process. With this purpose, the research was conducted using research and development methods. This research was held for 3 months at the Faculty of Education, Medan State University. The data was collected through a survey that was constructed by the appraisement of teaching materials for the principles of nonformal education based on higher order thinking skills from validator experts, language experts, instructional experts and students. The data was analyzed using descriptive-quantitative approach. The results of this research were (1) the procedure of teaching material development for the principles of nonformal education based on higher order thinking skills were valid to be used, and (2) The teaching materials of the principles of nonformal education were valid to be used in learning process for the subject of the principles of nonformal education.